HUBUNGAN KEWENANGAN PEMERINTAH PUSAT DAN DAERAH DALAM MENGURUS BIDANG PERTANAHAN DIHUBUNGKAN DENGAN HUKUM POSITIF - tri setiady (Fiat Justisia: Jurnal Ilmu Hukum, 2014)
Law Number 32 of 2004 of governmental authority in the land sector remains handed over to the autonomous region. Law Number 32 of 2004 requires the district/city governments to conduct business in the area of land as part of the implementation of regional autonomy and a mandatory affair because it is so fundamental with regard to rights and basic services citizens. The affairs of the land sector is very essential as it relates to the issue of community rights to land. Therefore, the government must provide the public with regard to the maintenance in the land sector. But on the other hand the government has not completed the handover of authority in the field of regulation of land through implementing regulations. Keywords: Central and Local Government Authority, Land and Legal Affairs Positive